The Impact of Rewards and Intrinsic Motivation on Performance of Employees in the Private Sector in Vietnam. - Thi Huong Mai; Thi Yen Mai (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
This study intended to evaluate and investigate motivation and its effects on performance of employees comprehensively in the working context. This research was conducted in the private sector in Vietnam through an online survey using a list of structured questionnaire. Data collected from the survey was processed by SPSS statistical analysis software. Data analysis results suggest that two factors tested: rewards and intrinsic motivation, both have significant and positive influences on performance of employees. Moreover, it admits the higher weight of intrinsic motivation out of rewards in the final performance of employees. In practice, the study provides a new approach in the way a reward system designed and how to maintain the motivation of employees. Last but not least, it suggests that motivation of employees should be taken into account when assigning a task or offering a job position.